A novel DO null allele with a c.268C>T (p.Gln90Stop) mutation in Japanese. Issue 2 (10th April 2015) - Onodera, T.; Tsuneyama, H.; Ogasawara, K.; Isa, K.; Satake, M.; Tadokoro, K.; Uchikawa, M.
<x xml:space="preserve">Abstract</x> The Dombrock blood group system consists of two antithetical antigens, Doa (DO1) and Dob (DO2), and seven high‐prevalence antigens, Gya (DO3), Hy (DO4), Joa (DO5), DOYA (DO6), DOMR (DO7), DOLG (DO8) and DOLC (DO9). Doa/Dob polymorphism is associated with c.793A>G (p.Asn265Asp) in exon 2 of the DO (ART4) gene, and the corresponding alleles are named DO*01 and DO*02. The rare Donull or Gy(a−) phenotype lacks all Dombrock antigens, and the DO null alleles vary with both DO*01 and DO*02 backgrounds. We report a novel DO null allele, which has a c.268C>T (p.Gln90Stop) nonsense mutation with a DO*02 background identified from four unrelated Gy(a−) Japanese individuals.